1998
DOI: 10.1073/pnas.95.16.9319
|View full text |Cite
|
Sign up to set email alerts
|

MEKK1 activates both IκB kinase α and IκB kinase β

Abstract: A critical step in the signal-induced activation of the transcription factor NF-B is the site-specific phosphorylation of its inhibitor, IB, that targets the latter for degradation by the ubiquitin-proteasome pathway. We have previously shown that mitogen-activated protein kinase͞ERK kinase kinase 1 (MEKK1) can induce both this site-specific phosphorylation of IB␣ at Ser-32 and Ser-36 in vivo and the activity of a high molecular weight IB kinase complex in vitro. Subsequently, others have identified two protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
298
2
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(308 citation statements)
references
References 31 publications
7
298
2
1
Order By: Relevance
“…GCK has been implicated in TRAF2-mediated MEKK1 activation, thereby regulating both AP1 and NF-kB pathways (Kyriakis, 1999;Lee et al, 1998;Yuasa et al, 1998). Poor expression levels of GCK in the early-phase melanoma cells have been identi®ed as the primary reason for impaired JNK and NF-kB activity.…”
Section: Discussionmentioning
confidence: 99%
“…GCK has been implicated in TRAF2-mediated MEKK1 activation, thereby regulating both AP1 and NF-kB pathways (Kyriakis, 1999;Lee et al, 1998;Yuasa et al, 1998). Poor expression levels of GCK in the early-phase melanoma cells have been identi®ed as the primary reason for impaired JNK and NF-kB activity.…”
Section: Discussionmentioning
confidence: 99%
“…When overexpressed, MEKK1 stimulates the activities of both IKKa and IKKb in transfected HeLa cells and directly phosphorylates the IKKs in vitro (Lee et al, 1998). Furthermore, a dominant-negative mutant of MEKK1 partially blocks activation of the IKK complex by TNFa (Hirano et al, 1996;Lee et al, 1997).…”
Section: Inhibitors That Act Upstream Of the Ikk Complexmentioning
confidence: 99%
“…Overexpression of NIK potently induces NF-kB (Malinin et al, 1997), primarily through the non-canoncial pathway (Scheidereit, 2006). In addition, some studies have demonstrated that MEKK1 is activated by TNFa and IL-1 and can potentiate the stimulatory effect of TNFa on IKK and NF-kB activation (Hirano et al, 1996;Lee et al, 1998).…”
Section: Inhibitors That Act Upstream Of the Ikk Complexmentioning
confidence: 99%
“…37 These kinases include NIK 38 and mitogen-activated protein kinase/extracellular signal-regulated kinase kinase 1. 39 Dominant interfering mutants of IkBa and IkBb and kinase-deficient mutants of IKKa, IKKb and NIK were tested for their ability to inhibit Tax-mediated activation of survivin-driven reporter gene. Expression of these various inhibitory mutants partly inhibited the activation of the survivin promoter by Tax (Fig.…”
Section: Tax Transactivation Of Survivin Promotermentioning
confidence: 99%